A atitude retórica no diálogo Górgias de Platão - Guimarães, Henrique Nascimento (Universidade Federal de São Carlos, 2020)
This work explores the tension between Philosophy and Rhetoric in Plato's Gorgias dialogue. For this, the work seeks to understand what Plato is talking about the activity performed by Gorgias and his pupils and the reason they do not have a technique (tekhne) but an activity conducted by experience (empeiria). The work seeks to elucidate what frankness (parrhesia) is and why the rhetoric promotes only flattery (kolakeia) and its meaning. The work seeks to justify with these elements the reason why the rhetoric does not defend justice like the philosopher, but freedom (eleutheria).
The rhetorical attitude in Plato's Gorgias dialogue
Keywords: Platão; Górgias; Retórica; Plato; Gorgias; Rhetoric; Parrhesia; Eleutheria; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA